A Health Informatics Reporting System for Technology Illiterate Workforce Using Mobile Phone - Durrani, Muhammad Imran Afzal; Qureshi, Noman Sohaib; Ahmad, Nadeem; Naz, Tabbasum; Amelio, Alessia (Applied Clinical Informatics, 2019)
Background The reduction and control over neonatal, infant, and maternal mortality is a collective mission of the World Health Organization under United Nations.Methods This article summarizes the automation of verbal autopsy reporting for neonatal, infant, and maternal mortality with primary focus on user-centered design for technologically illiterate workforce with minimum available resources. The diminution in neonatal, infant, and maternal deaths is not possible until grassroot level quality data are available for mortality. The estimated data are less effective for developing countries like Pakistan because it has heterogeneous demographic pockets with respect to mortality causes. The Neonatal, Infant, and Maternal Death E-surveillance System is a project in which a real-time reporting system is innovated that is useful in detecting the causes of mortality and effective in adopting appropriate countermeasure policies. In a pilot study, the system was implemented initially in nine districts of Punjab, Pakistan. The initial system was refined after getting detailed feedback from district management staff including Lady Health Workers and Lady Health Supervisors. The refined surveillance system was finally implemented in all 36 districts of Punjab, Pakistan.Results The results exhibited 31% improvement in infant data collection and 6% improvement in maternal data collection regarding mortality.Conclusion This research will be helpful in achieving the milestone of gathering real-time mortality data from grassroot level using user-centered design methodology.
Keywords: human–computer interaction; user-centered design; interfaces and usability; technologically illiterate workforce; verbal autopsy data collection